GURU PENDIDIKAN AGAMA KRISTEN DAN PENGGUNAAN KECERDASAN BUATAN: LITERATURE REVIEW - Kasingku, Juwinner; Robert Siby (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the perceptions of Christian Religious Education (CRE) teachers regarding the use of Artificial Intelligence (AI) in the learning process. The rapid development of AI in the field of education has brought significant changes to teaching and learning practices, including in religious education. On the one hand, AI offers various advantages, such as more personalized learning, the provision of interactive learning materials, and greater efficiency in managing teachers’ administrative tasks. On the other hand, CRE teachers face new challenges, particularly related to digital literacy demands, technological readiness, and ethical and spiritual responsibilities in using AI so that it does not conflict with Christian faith values. The purpose of this study is to identify the benefits and challenges of integrating AI into Christian Religious Education, as well as to examine the factors that influence teachers’ perceptions of this technology. This research employs a qualitative method using a literature review approach, in which data are obtained from books, scholarly journal articles, and relevant documents discussing AI in education and Christian Religious Education. The data are analysed thematically to identify patterns of perspectives, opportunities, and challenges. The findings indicate that, in general, CRE teachers hold a fairly positive attitude toward the use of AI, especially because of its potential to support adaptive and engaging learning. However, significant obstacles remain, including limited technological infrastructure, a lack of specialized training for teachers, and concerns about reduced personal relationships and students’ spiritual development. Therefore, it can be concluded that the successful integration of AI in Christian Religious Education largely depends on teacher readiness, technological support, and the wise and ethical use of AI, so that it truly serves as a supportive tool that strengthens students’ faith formation and character development rather than replacing them.